FAKTOR-FAKTOR YANG MEMPENGARUHI ISLAMIC SOCIAL REPORTING PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR PADA INDEKS SAHAM SYARIAH INDONESIA (ISSI) TAHUN 2014-2016 - Eka Susanti; Puji Nurhayati (INVENTORY: JURNAL AKUNTANSI, 2018)
This study aims to obtain empirical evidence on the analysis of factors affecting Islamic Social Reporting (ISR). Factors used include company size, profitability, industry type, and as an additional variable that is sharia securities. The measurement of Islamic Social Reporting (ISR) is based on the category of Islamic reporting to measure the Index ISR viewed from the company's annual report. The population in this study are all companies listed in Indonesia Sharia Shares Index (ISSI) in 2014-2016. Sampling method used in this research is purposive sampling method. The total sample used in this study as many as 10 companies. Data analysis was done by classical assumption test and hypothesis testing by multiple regression method. The results of this study indicate that the company size factor, Profitability No significant positive effect on ISR in Indonesia. While the type of industry, Securities have a significant effect on ISR in Indonesia.Keyword : Islamic Social Reporting, List of Sharia Securities, ISR Index and company’scharacteristic